The correct authorship and date of lizard names Teiinae, Tupinambinae,and Gymnophthalmidae - Costa, Henrique C.; Garcia, Paulo C.a.; Zaher, Hussam (Zootaxa, 2016)
Teiidae and Gymnophthalmidae are lizard families endemic to the Neotropical region (Vitt & Caldwell 2014), with about 150 and 245 valid living species, respectively (Uetz & Hošek 2015). Extinct teiid taxa are known from the Cretaceous to the Holocene (Albino 2005; Estes 1983b; Sullivan & Estes 1997). The authorship of Teiidae is undoubtedly attributed to Gray (1827) (ICZN 1985), but there is some confusion in literature regarding its subfamilies Teiinae and Tupinambinae. The same is true for Gymnophthalmidae. We investigated those issues through a literature review, found the source of mistakes and suggest what we consider be the correct authorship and dates for those family-group names.